Bahasa Indonesia - Ibad, Khairul (Maliki Interdisciplinary Journal, 2024)
banking is one of the business sectors most affected by the corona virus, both conventional and sharia banking. field research is the type of research used. this research is descriptive and qualitative, meaning it describes the subject matter. the author uses qualitative descriptive analysis to analyze this research data. during the covid-19 pandemic, the growth of sharia commercial banks experienced a decline in 2020, but is expected to recover in 2021. in terms of issue funding, the risk of issuance in 2021 will decrease due to more selective funding allocation. moreover, the dpk index, which consists of current accounts, deposits and savings, recorded a decline in 2020, but returned to normal in 2021. it can be concluded that sharia commercial banks also recorded a decline due to the corona outbreak throughout the world. however, after the covid-19 pandemic, the performance of islamic commercial banks has begun to gradually recover.